Impacts of micro- and nanoplastic exposure on the cardiovascular system: a systematic review focused on in vivo studies - Hikmawan Wahyu Sulistomo; Muhammad Reva Aditya; Athaya Rahmanardi Muhammad; Oktivani Adelathifa Rahma (All Life)
Microplastics and nanoplastics, degraded plastic polymers, are increasing in the environment, raising concerns about their potential health impacts, particularly on the cardiovascular system. This systematic review aimed to investigate the prospective effects of MPs and NPs on cardiovascular toxicity. This study was written following the PRISMA 2020 guidelines. The risk of bias in the included studies was assessed using the SYRCLE tool. Our review included 38 in vivo studies dating back from 2017 to 2024 from several databases, including PubMed, ScienceDirect, SpringerLink, Taylor & Francis, ProQuest, and Wiley Online Library, with inclusion criteria of (PECOS) (1) Population: Animal; (2) Exposure: All types of exposure to micro nanoplastics; (3) Comparison: Placebo/ Control; (4) Outcome: Cardiotoxicity, inhibition of development of cardiovascular tissue, oxidative stress, inflammation, and abnormal structure; and (5) Study design: In vivo experimental study. Studies reveal that MPs and NPs cause cardiovascular toxicity through deposition, morphological changes, biomarker alterations, metabolism changes, and genetic regulation related to injury, inflammation, and oxidative stress. This study is limited to the comparison of the different particle sizes, dose of exposure, and duration of exposure effects toward cardiotoxicity, and does not compare the different effects of toxicity between different particle types.